2005
DOI: 10.1167/iovs.04-0906
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Parameters of Retinal Circulation Measured by Laser Doppler Velocimetry and a Marker of Early Systemic Atherosclerosis

Abstract: The present findings from this pilot study suggest that the retinal circulatory parameters measured by LDV may be associated with systemic atherosclerosis. These results support recent studies showing an association between retinal microvascular changes and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…49 Interestingly, a significant and independent association between retinal circulation parameters and carotid IMT, a surrogate marker of atherosclerosis, has been described recently in patients with coronary artery disease. 50 In the present study, increased carotid IMT was associated independently with increased WML. This is consistent with the Cardiovascular Health Study data, which showed that increased carotid IMT was independently associated with increased WML.…”
Section: Discussionsupporting
confidence: 58%
“…49 Interestingly, a significant and independent association between retinal circulation parameters and carotid IMT, a surrogate marker of atherosclerosis, has been described recently in patients with coronary artery disease. 50 In the present study, increased carotid IMT was associated independently with increased WML. This is consistent with the Cardiovascular Health Study data, which showed that increased carotid IMT was independently associated with increased WML.…”
Section: Discussionsupporting
confidence: 58%
“…Using these two independent retinal circulatory parameters, we can evaluate changes in the WSR in the retinal circulation. 35 Most previous studies 1,2,32 did not report WSR data, which is an index of wall shear stress, 28 because the vessel diameter and blood velocity were not measured simultaneously as a result of methodologic difficulties. Only one study reported decreased WSR in the retinal arterioles in response to systemic hyperoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Functional hemodynamic indices such as max:min velocity ratio, resistivity index, pulsatility index, and WSR have been investigated previously using the retinal vasculature. 24,39,40 Increased peripheral arterial stiffness (measured in the arm and ankle) has been positively correlated with severity of DR. 41 Resistivity and pulsatility indices were not used in this study because of the extraneous influence of downstream impedance. 42,43 WSR is a measure of shear stress (i.e., shear stress ϭ WSR ⅐ viscosity).…”
Section: Discussionmentioning
confidence: 99%